Computational Mechanics of Structures and Materials - Bacciocchi, Michele; Tarantino, Angelo Marcello; Luciano, Raimondo; Majorana, Carmelo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The vast number of recently published research papers on computational and numerical methods for solving various structural problems proves that this topic has great potential, and the further advancements that can be accomplished are still numerous.This reprint contains innovative investigations dealing with accurate, reliable, and effective numerical approaches in the field of both structural mechanics and the mechanics of materials.In particular, these studies present a numerical analysis focused on the development of finite-element or finite-element-based methods for novel problems, as well as different computational techniques involving the solution of those problems that require the development of numerical methods to obtain approximate but accurate solutions.In any circumstance, the contributing authors have emphasized the novelty of their approaches, highlighting the improvements with respect to the existing literature. Much attention has also been dedicated to the numerical investigations of advanced and innovative materials, as well as multiscale analyses, employed in many engineering fields, such as civil, mechanical, and aerospace engineering.